LPIA COURSE ON PAYMENT SYSTEM USING VISUAL BASIC 6.0 - Iwan Junaidi; Jalinas Jalinas, SKom, MM (Jurnal Sistem Informasi, 2002)
For in terms of data security, file-file security can be maintained with a good ideabecause there are data protection thus reducing damage and loss of data. Theavailable funds sufficient to support the proposed system in order to expedite thepayment process activity courses that help the financial management in dataprocessing.